Investigate all kinds of flavorings used in some local food products and imported - Baghdad Science Journal (مجلة بغداد للعلوم)
In this study, the investigation of flavorings used in 567 model of local food products and imported in our local markets through information contents cards media shoddy standard Iraqi has been found that foods that appeal to children of sugar confectionery and Crapt and other barely Atkhalo of flavorings used that lead tohealth risks